Rapid Synthesis and Characterization of Silver Nano Particles by Novel Pseudomonas sp.Ã¢â‚¬Å“ram bt - 1Ã¢â‚¬Â - Balakrishnan2*, Muthukannan Rammohan1, Karuppiah (Journal of Ecobiotechnology, 2011)
The usage of micro organism for the production of Bio – metallic Nano particles is the promising field of biotechnology and their potential .applications from agriculture to medicine are Inevitable. In the present study, we reported that the Screening and molecular identification of a novel strain psuedomoans sp. ram bt-1 from marine sample (Coast of Bay of Bengal) through 16s rRNA ribotyping (Gen bank accession number:GU 591788) . Synthesis of silver nanoparticles by this new strain at the intracellular level has been charecterized by UV-Spectrophotometer,X-Ray diffraction, and Scaniing electron microscope analysis.SEM observations are revealed that silver nano particles are having poly dispersed and different sizes are ranging from 20 to 100 nm in size. (XRD) results have shown that these nanoparticles exhibit a face-centered cubic crystal structure. To the best of our knowledge, this is the first report of intracellular rapid production of silver nanoparticles are synthesized and characterized by marine strain Pseudomonas sp.